Phase segregated Cu2−xSe/Ni3Se4 bimetallic selenide nanocrystals formed through the cation exchange reaction for active water oxidation precatalysts. Issue 6 (3rd January 2020) - Kim, Sungwon; Mizuno, Hiroki; Saruyama, Masaki; Sakamoto, Masanori; Haruta, Mitsutaka; Kurata, Hiroki; Yamada, Taro; Domen, Kazunari; Teranishi, Toshiharu
Abstract : Bimetallic selenide nanocrystals formed by cation exchange reaction work as a precursor of efficient water oxidation electrocatalyst. Abstract : Control over the composition and nanostructure of solid electrocatalysts is quite important for drastic improvement of their performance. The cation exchange reaction of nanocrystals (NCs) has been reported as the way to provide metastable crystal structures and complicated functional nanostructures that are not accessible by conventional synthetic methods. Herein we demonstrate the cation exchange-derived formation of metastable spinel Ni3 Se4 NCs (sp-Ni3 Se4 ) and phase segregated berzelianite Cu2− x Se (ber-Cu2− x Se)/sp-Ni3 Se4 heterostructured NCs as active oxygen evolution reaction (OER) catalysts. A rare sp-Ni3 Se4 phase was formed by cation exchange of ber-Cu2− x Se NCs with Ni 2+ ions, because both phases have the face-centered cubic (fcc) Se anion sublattice. Tuning the Ni : Cu molar ratio leads to the formation of Janus-type ber-Cu2− x Se/sp-Ni3 Se4 heterostructured NCs. The NCs of sp-Ni3 Se4 and ber-Cu2− x Se/sp-Ni3 Se4 heterostructures exhibited high catalytic activities in the OER with small overpotentials of 250 and 230 mV at 10 mA cm −2 in 0.1 M KOH, respectively. They were electrochemically oxidized during the OER to give hydroxides as the real active species. We anticipate that the cation exchange reaction could have enormous potential for the creation of novel heterostructured NCs showing superior catalytic performance.